2015
DOI: 10.1097/aog.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Labor Cervical Examination Simulation in Medical Student Education

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…Most previous reports of simulation for medical students in OBGYN have focused training around the third-year medical students OBGYN clerkship. [ 10 , 11 , 14 ] This is in contrast to our curriculum in which we focused on MS2 with the simulation occurring in the fall, approximately 7 to 8 months prior to starting clinical rotations. Our goal was to provide early exposure and experience to clinical concepts and procedures, which could lead to more integration of basic science concepts and better preparedness for the clinical rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous reports of simulation for medical students in OBGYN have focused training around the third-year medical students OBGYN clerkship. [ 10 , 11 , 14 ] This is in contrast to our curriculum in which we focused on MS2 with the simulation occurring in the fall, approximately 7 to 8 months prior to starting clinical rotations. Our goal was to provide early exposure and experience to clinical concepts and procedures, which could lead to more integration of basic science concepts and better preparedness for the clinical rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to provide early exposure and experience to clinical concepts and procedures, which could lead to more integration of basic science concepts and better preparedness for the clinical rotation. Furthermore, unlike most previous reports that focused mainly on obstetrical procedures, [ 10 , 11 , 14 ] we expanded our curriculum to Gynecology in the last 2 years to include stations on family planning, contraception, and IUD insertion. Lerner et al also provided an extensive OBGYN simulation that in addition to obstetrics procedures included IUD insertion, hysteroscopy/cystoscopy, colposcopy/LEEP, and circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited studies that showed the positive effects of simulation directly (22). There is also a limited cases of evidence about how many skills and competencies could be obtained after simulation training (23). Thus, we have insufficient knowledge about the case after the simulation, especially in terms of competence statute, the number of practice sessions that is needed, and competence could be got and if simulation could decrease future malpractice or not.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, simulation training has been widely used in the field of obstetrics. Previous studies have demonstrated that simulation training could improve medical students’ perceived comprehension of several common obstetric procedures, increase their confidence with vaginal deliveries, and improve their accuracy in cervical examination . Brady et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that simulation training could improve medical students' perceived comprehension of several common obstetric procedures, 7 increase their confidence with vaginal deliveries, 8,9 and improve their accuracy in cervical examination. 10,11 Brady et al 12 also showed that progressive and medium fidelity simulation contributes to the development of integrated and global clinical skills among midwifery students.…”
Section: Introductionmentioning
confidence: 99%